Borges en Penguin (El Hilo de la Fabula, 2015)
Most of Jorge Luis Borges’ writings were first published in reviews or newspapers before being included in an edited volume. For this publication Borges submitted his writings to a selection process which finished by excluding an important part of it. Apparently he perceived his oeuvre as a conscious act of production which aims at the transmission of literary concepts. During the past 20 years however much of the material which had been considered lost has been rediscovered, and has been edited under different forms until a complete publication of his work was achieved. Borges editions in other languages than spanish however did not follow this model; the texts were collected and edited following other logics, that would answer to the specific history of Borges reception in other countries and languages. In 2010, Penguin proposed a parcial reedition of Borges in english, in a serie of volumes based on a variety of criteria, giving autonomy to new aspects of Borges work. This paper analyses the goals and effects of this editions.